Draft Tenth Five Year Plan 2002-07 Volume-II, Government of Orissa - Planning Commission (Planning Commission, 2002)
GN Statement (Abstract to Annexure-I), Proposed Outlays, Physical Targets and Achievements, Proposals for Spillover and ongoing Programmes/ Projects as in Annexure-I, Proposals for Maximising benefits of completed Programmes/Projects (As on 31.3.2000), Proposals for Programmes/ Projects-New Schemes, Summary Statement-Proposals for Progrmmes/ Projects, Statement regarding Externally Aided Projects, Outlays (By heads of Development) for District Plans, Centrally Sponsored Schemes, Prime Minister’s Gramodaya Yojana- Outlay/ Expenditure, Tribal Sub-Plan (T.S.P.) - I - Proposals for T.S.P.- Financial outlays, Tribal Sub-Plan (T.S.P.) - II - Proposals for T.S.P.- Physical Targets, Special Component Plan for Scheduled Castes (S.C.P)- I - Proposals for S.C.P.-Financial Outlays, Special Component Plan for Scheduled Castes (S.C.P.)- II- Proposals for S.C.P.- Physical Targets, Financial Outlays/Expenditure for Voluntary Sector, Women Component (WC) in the State Plan Programmes-I- Financial Outlays: Proposals for Women Component, Women Component (WC) in the State Plan Programmes-II- Physical Targets: Proposals for Women Component
Draft Tenth Five Year Plan 2002-07 Volume-II, Government of Orissa
Government of Orissa